THE EFFECTIVENESS OF THE QUANTUM TEACHING MODEL ASSISTED BY THE RAINBARD MEDIA ON THE RESULTS OF MATHEMATICS LEARNING - Hermawati, Fitria Ayu; Sari, Elok Fariha; Sismulyasih SB, Nugraheti (Elementary School Teacher, 2019)
This type of research is experiment research that aims to test the effectiveness of the quantum teaching model by assisted rainbow board to result of mathematics studies outcomes of 4th grade students of elementary school of the Ikan Mas Cluster, North Semarang. This research used quantitative method with experiment design with nonequivalent control group design. The sample technique was cluster random sampling of 128 participantes. Data collection used test, observation and documentation. The hypothesis test result showed that tcountËƒttabel (2.128Ëƒ 2.037) which mean quantum teaching model assisted by rainbow boardis was more effective to result of social studies outcomes of 4th grade students. The experiment class n-gain test result 0.734 belong to high criterion while control class n-gaint test result 0.481 belong to medium criterion